(untitled) (Biological Sciences - PJSIR, 2022)
Preparation of a high-viscosity syrup that contained 80 and 85% sucrose was studied. Dextran produced by a locally isolated strain of Leuconostoc mcsenieroides and its spent culLure medium were used as stabilizers. The spent culLure medium with a solid content of 11.5% contained 44% dextran, 40% reducing sugars and 12% non-reducing sugars. The stabilizing properties of dextran and the spent culLure medium were compared with those of commercial stabilizers such as liquid glucose, sodium alginate and carboxymeLhyl cellulose.